2009
DOI: 10.1016/j.jtbi.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling promoter search by E. coli RNA polymerase: One-dimensional diffusion in a sequence-dependent energy landscape

Abstract: We present a biophysical model of promoter search by Escherichia coli RNA polymerase. We use an unconventional weight matrix derived from promoter strength data to extract the energy landscape common to a large set of known promoters. This exhibits a continuous strengthening of the binding energy when approaching the transcription start site from either side. During promoter search, the RNA polymerase slides along the DNA double helix (one-dimensional diffusion) after randomly binding to it. We discuss the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Additionally, the presence of weaker sites flanking a strong binding site could lead to a funnel effect where the molecules are directed to the strong binding site and retained there for longer times [61–63] . However, it is controversial whether TFs can bind at all to weak binding sites [64] , which is a necessary assumption required for the funnel effect hypothesis.…”
Section: Mechanisms By Which Homotypic Clusters Could Influence Gene mentioning
confidence: 99%
“…Additionally, the presence of weaker sites flanking a strong binding site could lead to a funnel effect where the molecules are directed to the strong binding site and retained there for longer times [61–63] . However, it is controversial whether TFs can bind at all to weak binding sites [64] , which is a necessary assumption required for the funnel effect hypothesis.…”
Section: Mechanisms By Which Homotypic Clusters Could Influence Gene mentioning
confidence: 99%
“…The possibility of speed-up due to a funnel has been already proposed in the literature. A theoretical study of RNAP, ignoring the effects of fluctuations, showed that energy gradients directly translate into a deterministic bias toward the target ( 27 ). A computational study, based on Brownian dynamics simulations of a coarse-grained model of the TF–DNA complex, demonstrated that organizing binding energies in a funnel reduces the search time with respect to the case of randomly organized binding energies ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Различные группы исследователей рассматривали в качестве возможных промоторных детерминант такие физические свойства и геометрические характеристики молекулы ДНК, как электростатический потенциал [Polozov et al, 2005;Камзолова и др., 2009;Sorokin et al, 2006;Kamzolova et al, 2005;Polozov et al, 1999], устойчивость к суперскрученности [Wang, Benham, 2006;Benham, 1996;Benham et al, 1997], термодинамическую стабильность [Jost, Everaers, 2009;Yeramian, 2000], изгибность цепи [Rohs et al, 2009], способность формировать изломы [Jensen et al, 1999], а также доступность и расположение доноров и акцепторов водородных связей в большой борозде промоторной ДНК [Weindl et al, 2009]. Все эти характеристики играют важную роль на различных этапах взаимодействия ДНК и РНК-полимеразы: при первичном узнавании, формировании комплекса «белок-ДНК», синтеза первичного РНК-транскрипта и формировании элонгирующего комплекса.…”
Section: Introductionunclassified